Pollination Systems of Palms (Arecaceae) - Henderson, Andrew (Journal of Pollination Ecology, 2024)
A review is given of pollination systems in the palm family (Arecaceae). Pollination studies of 149 species (6% of the total number) in 60 genera (33% of the total number) are reviewed. The majority of these studies (75%) are of Neotropical palms. In the sample of 149 species, approximately 52% are beetle-pollinated, 27% bee-pollinated, 7% fly-pollinated, 5% thrips pollinated, 5% wind pollinated, 3% moth-pollinated, and 1% mammal-pollinated. A few other species may be bird-pollinated. Adaptations of inflorescences and flowers to pollinators are not readily apparent except for a general tendency for bee-/fly-pollinated species to have longer, open inflorescences and beetle-pollinated species to have shorter, condensed inflorescences. Classical pollination syndromes are not useful in describing, classifying, or predicting palm pollination systems because of numerous exceptions. The degree to which palm pollination systems may be considered specialized or generalized is unclear. There appear to have been numerous, bidirectional shifts in palms between beetle pollination and bee/fly pollination, and less often shifts to other pollinators. Beetle-pollinated inflorescences are usually visited by bees, and bee-pollinated inflorescences are usually visited by beetles. It seems likely that many species of palm, irrespective of pollinator, have their inflorescences used as brood-sites by beetles.